Penerapan Jaringan Distribusi Sistem District Meter Area (DMA) SPAM Semarang Barat dalam Optimalisasi Penurunan Kehilangan Air Ditinjau dari Aspek Teknis dan Finansial (Studi Kasus : Area Pelayanan Reservoir Manyaran 1) - Bagus Tri Buko; Anik Sarminingsih; Budi Prasetyo Samadikun (Jurnal Ilmu Lingkungan, 2022)
Drinking water is one of basic human needs that is very important to  improve the quality of human life and economic growth of a region. PDAM Tirta Moedal, Semarang City developed “SPAM Semarang Barat”  1,000 liters/sec to serve water demand in West Semarang, Ngaliyan and Tugu sub-districts. Water losses in PDAM Kota Semarang is still at 40.10%, indicating that water distribution is not optimal. DMA is a strategy in managing water loss, especially real water loss, by dividing an open water supply network into isolated zones with smaller water meter. In this study, a technical and financial study was conducted regarding the implementation of DMA in the SPAM Semarang Barat distribution specifically for the Manyaran 1 Reservoir service area . The real water loss is caused by visible or invisible leakage of distribution pipes (background leakage). The billed authorized consumption is estimated at 4,189,607 m3/year, the unbilled authorized consumption is 7,361 m3/year. Apparent water loss is estimated at 147,455 m3/year or about 2%, while real water loss is around 2,172,896 m3/year or about 34%. The Infrastructure Leakage Index or ILI for the Manyaran 1 Reservoir distribution is 49. It means that PDAM is wasting some resource, which caused losses.  Epanet 2.0 shows that peak hours pressure is between 30 – 70 m, there is no pressure below 10 m. Velocity at peak hours is in the range of 0.1 – 1.0 m/s. The investment requirement for DMA development in the Manyaran 1 service area Rp. 18,786,292,828, - for development of services as much as 5,843 SR. District Meter Area in distribution system is estimated to reduce the leakage rate by up to 20%, so that the potential revenue will increase by Rp. 26,083,764,633,-. It means that DMA is one of ways to solve water leakage problem.